ETIKA DALAM ASESMEN PSIKOLOGI UNTUK MENINGKATKAN KUALITAS LAYANAN BIMBINGAN DAN KONSELING - Nailunnajwa (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
Psychological assessment is one of the essential aspects of the guidance and counseling process, serving to understand the client’s characteristics, needs, and potential in a comprehensive manner. Through assessment, counselors can obtain an objective picture of the client’s psychological condition, which becomes the foundation for formulating appropriate interventions. However, in practice, psychological assessment is not free from complex ethical challenges. Two main aspects that often draw attention are the confidentiality of assessment data and the counselor’s effort to maintain objectivity during the interpretation process. Violations of confidentiality principles can undermine client trust and diminish professional credibility, while a lack of objectivity may lead to bias in evaluation and decision-making. This article discusses the importance of applying ethical principles at every stage of psychological assessment from data collection, interpretation, to the communication of results. Through theoretical review and case study analysis, this article also outlines strategies that counselors can use to address ethical dilemmas, such as adherence to professional codes of ethics, continuous supervision, and the enhancement of ethical awareness. The findings emphasize that a deep understanding of ethics in psychological assessment is crucial for building a healthy professional relationship between counselor and client, as well as for maintaining integrity and moral responsibility within guidance and counseling practice.